A review of various types of male contraception - Yeonhee Pyo; Ki Han Kwon (Journal of Men's Health)
Birth control options for men are limited to only condoms and vasectomies. This review focuses on various types of male contraceptives for adequate fertility control and family planning by mutual understanding of couples (healthy family planning). Male contraceptive methods include hormonal and non-hormonal contraceptives, condoms, vasectomies, and using active ingredients from plants. Contraception in men is related to progesterone concentration, sperm count, sperm motility, sperm maturation and sperm viability. Studies are required on no side-effect-safe contraceptives for men that control serum progesterone levels, however do not increase oxidative stress. In conclusion, this article covers hormonal, non-hormonal, and plant-based male contraception in addition to the popular condoms and vasectomy. Furthermore, it includes partial description of the variety and mechanisms of male contraceptive methods available to men.